Statistics for the social sciences - Sirkin, R. Mark (SAGE Publications, 2006)
"Like previous editions, this Third Edition continues to help build students' confidence and ability in doing statistical analysis by slowly moving from concepts that require little computational work to those that require more. Author R. Mark Sirkin once again demonstrates how statistics can be used to help students come to appreciate real-world applications rather than fearing them. Statistics for the Social Sciences emphasizes the analysis and interpretation of data to give students a feel for how data interpretation is related to the methods by which the information was obtained. The book includes lists of key concepts, chapter exercises, topic boxes, and more." "Statistics for the Social Sciences is an excellent text for advanced undergraduate and graduate students studying statistics across the social sciences. It can also be used in research methods courses that cover quantitative applications in some depth"